Respon Imunogenitas Antibodi Poliklonal IgY terhadap Protein Adhesi Pili 95 kDa Shigella dysenteriae - asihanti rosita ferdiana; Enny Suswati; Kristianningrum Dian Sofiana (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
Shigella dysenteriae is the most frequently cause of deaths of dysentery cases in infants and toddlers. Shigella dysenteriae has a pili that act as an adhesin molecule and will detect in human body as antigens which is involved in producing antibodies. This study was conducted to prove that Shigella dysenteriae pili adhesion protein 95 kDa is immunogenic. This was an experimental laboratory study with quasy experimental design in vitro. The study began with mice erythrocyte cell isolation, IgY polyclonal antibodies isolation, mice intestinal enterocytes cell isolation, hemagglutination inhibition test, and adhesion inhibition test. The haemagglutination inhibition test showed that the pili adhesion protein 95 kDa of S. dysenteriae able to inhibit the haemagglutination of erythrocytes mice Balb/C up to ½ dilution. While, the adhesion inhibition test revealed that the fewer of antibody concentration on enterocytes, the greater bacteria attached. According to the linear regression test results, the index adhesion value increased along with the decreased of antibody concentration. In conclusion, pili adhesion protein 95 kDa from S. dysenteriae was immunogenic and could inhibit the hemagglutination and adhesion between S. dysenteriae and mice enterocytes cells. Keywords: immunogenicity, IgY polyclonal antibody, Shigella dysenteriae, pili adhesion protein.